2005
DOI: 10.1002/ijc.21393
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of linoleic acid on transformation of IEC6 intestinal cells by in vitro azoxymethane treatment

Abstract: The effect of linoleic acid (LA) on growth and transformation of IEC6 intestinal cells was examined. IEC6 cells expressed mRNAs of 15-lipooxygenase (LOX15) and peroxisome proliferator-activated receptor (PPAR)c but not COX-2. Cell growth was suppressed by LA in a dose-dependent manner in IEC6 cells. Threeweek treatment with LA provided IEC6 cells a quiescent state. LA-induced growth inhibition was abrogated by exposure to antisense S-oligodeoxynucleotides (S-ODNs) for LOX15 and/or PPARc. In an in vitro carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Others have shown PPARg activation with 9,11-conjugated linoleic acid (45,46), and because PPARg is known to induce itself, this is a simple explanation for why elevated PPARg levels were observed. In another study that supports an anticarcinogenic role for PPARg in colon carcinogenesis, immortalized rat intestinal IEC6 cells experience reduced proliferation with linoleic acid (47). These changes are reversible when PPARg expression is inhibited by RNA knockdown techniques, thus suggesting a tumor-suppressive role for PPARg constitutive expression.…”
Section: Clinical-translational Advancesmentioning
confidence: 94%
“…Others have shown PPARg activation with 9,11-conjugated linoleic acid (45,46), and because PPARg is known to induce itself, this is a simple explanation for why elevated PPARg levels were observed. In another study that supports an anticarcinogenic role for PPARg in colon carcinogenesis, immortalized rat intestinal IEC6 cells experience reduced proliferation with linoleic acid (47). These changes are reversible when PPARg expression is inhibited by RNA knockdown techniques, thus suggesting a tumor-suppressive role for PPARg constitutive expression.…”
Section: Clinical-translational Advancesmentioning
confidence: 94%
“…Exposure to PPAR-␥ antisense S-oligodeoxynucleotide reversed the LA-induced quiescence in both MKN28 and Colo320 cells. PPAR-␥ antisense treatment reversed LA antitumor effects in azoxymethane-induced carcinogenesis and peritoneal metastasis [15,29] . In the present study, LA-treated cells showed the same alteration of protein levels to those in cells treated with PPAR-␥ ligands, TGZ and CLA.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PPAR-␥ affects expression of EGFR, cyclin D 1 [34] and Bax [35,36] . We previously reported that LA and CLA decrease the expression of EGFR and transforming growth factor ␣ , and increase Bax expression [15,29,37] . These alterations might be associated with cell growth inhibition and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies show that PPAR-␥ activation by troglitazone and rosiglitazone (synthetic PPAR-␥ ligands) synergises with simultaneous inhibition of X-linked inhibitor of apoptosis protein (endogenous apoptotic inhibitor, overexpressed in colon cancer) in treatments of colon cancer in mice xenograft models [101,102] . Growth of IEC6 colon cancer cells (expressing 15-LOX-1 and PPAR-␥ but not COX-2), induced by a potent carcinogen, azoxymethane, was successfully controlled by linoleic acid in a dose-dependent manner in in vitro studies [103] . Taken together, these results strongly support the notion that both linoleic acid and synthetic PPAR-␥ ligands may be beneficial in colon cancer, but remains to be confirmed in man.…”
Section: Therapeutic Targeting Of Fatty Acid Metabolism In Colon Cancermentioning
confidence: 99%